Matching-Based Minimum-Cost Spare Cell Selection for Design Changes - Jiang, Iris Hui-Ru; Chang, Hua-Yu; Chang, Liang-Gi; Hung, Huang-Bi (My University, 2009)
Metal-only ECO realizes the last-minute design changes by revising the photomasks of metal layers only. This task is challenging because the pre-injected spare cells are limited both in number and in cell types. This paper proposes a matching-based EGO synthesizer, named EGOS, that correctly implements the incremental design changes using the available spare cells as well as tries to reduce the prohibitive photomask cost at the same time. The experiments are conducted on five industrial testcases. ECOS uses less photomask costs to complete design changes for all cases than the direct method that transforms the widely-used hand-editing procedure into an automatic one.
Keywords: EGO; spare cells; resynthesis; physical synthesis; matching